Performance of dairy calves fed diet containing Ca-palm oil fatty acid and Sapindusrarak fruit - Elizabeth Wina; Yenni Widiawati; Budi Tangendjaja (Jurnal Ilmu Ternak dan Veteriner, 2018)
Calcium salts of palm oil fatty acid (Ca-FA) is a high dense energy source that is protected from degradation in the rumen. Sapindusrarak fruits (SrF) contain high level of saponin and have been reported to increase body weight sheep or cattle and reduced protozoa population in the rumen. This experiment used a combination of Ca-FA and SrF to improve the performance of weaned dairy calves. Thirty two heads of weaned Indonesian Holstein were used in factorial block design experiment (2 x 2). The first factor was Ca-FA(with 2.5% and without addition of Ca-FA)  while the second factor was SrF (with 0.3% and without addition of SrF in total diet) and sex of the animal as block was applied. The feed as total mixed ration contained crude protein (CP)17%, total digestible nutrien (TDN)minimum 69%, Net energy for maintenance 1.70Mcal/kg and Net energy for gain 1.03Mcal/kg. It was fed 3% of body weight of the animals for 14 weeks included 2 weeks of adaptation period. Feces collection for measuring digestibility of feed was conducted at the end of experiment. Average daily gain (ADG) of calves received SrF was higher than without SrF (896.9 vs 853.7 g/day) while ADG received CaFA was lower than without CaFA (860.6 vs 890 g/day) but both effects were not significantly different (P>0.05). DM intake due to SrF treatment tended to be higher than control treatment (4.4 vs 4.3 kg/day). DM digestibility was not different among treatments. In conclusion,calves received supplementation of 0.3% SrF fruit in the diet had similar average daily gain with those given unsupplemented diet but had reduced diarrhea cases.